2011
DOI: 10.1245/s10434-011-2008-5
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Predictors of Nipple–Areola Complex Involvement for Patients Undergoing Mastectomy for Breast Cancer

Abstract: Clinical and imaging abnormalities at the NAC are the only independent preoperative predictors of NAC pathology, and the absence of these factors conveys a low probability of NAC involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 20 publications
2
33
0
1
Order By: Relevance
“…The rates of tumour NAC involvement in the literature are inconsistent [14][15][16][17][18][19][20][21] likely due to different pathological protocols for NAC evaluation and variable accuracy of clinical and pathological data collection. For example, a recent systematic review of the literature showed that only 6.4% of the nipple cores of 2477 NAC sparing mastectomies were involved with tumour [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of tumour NAC involvement in the literature are inconsistent [14][15][16][17][18][19][20][21] likely due to different pathological protocols for NAC evaluation and variable accuracy of clinical and pathological data collection. For example, a recent systematic review of the literature showed that only 6.4% of the nipple cores of 2477 NAC sparing mastectomies were involved with tumour [13].…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of NAC involvement has been associated with several tumour characteristics such as retroareolar location, distance from the NAC, size, multifocality/mul ticentricity, grade, lympho-vascular invasion, extensive intraductal component and lymph-nodal status [14][15][16][17]. We recently showed that tumour-NAC distance measured by magnetic resonance imaging (MRI) of the breast is the key preoperative predictor of NAC involvement in a series of total mastectomies performed at our Institution [18].…”
Section: Introductionmentioning
confidence: 99%
“…The terminal duct lobular unit has been identified as the location for the development of all breast cancer, and a 2008 study identified the presence of terminal duct lobular units in the nipples of 9% of patients (10,11). The rate of occult malignancy detected in the NAC in mastectomy specimens has varied widely with studies reporting an incidence of 1-31% (12)(13)(14)(15)(16). Over the years, a number of prospective and retrospective studies have demonstrated a cancer recurrence rate in the NAC of up to 2%, with local recurrence rates ranging from 1-6% (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Accepted risk factors include large tumor size, short tumor-nipple distance, multifocal or multicentric location, lymphovascular or lymph node involvement, and positive HER2 status. 12,15,[23][24][25][26][27] Thus, NSM is most frequently used in cases of prophylaxis or early disease, although it has also been used safely in advanced disease. 28 The surgeon's decision to preserve the nipple at the time of NSM is guided by the results of an intraoperative subareolar biopsy, which is taken to rule-out occult nipple malignancy.…”
Section: Discussionmentioning
confidence: 99%